The Political Economy of Product Liability Reform - Epstein, Richard A. (American Economic Review, 1988)
The present body of product liability rules has been fashioned by common law judges, with an occasional assist from legislatures. The key premise of the present system is that freedom of contact, even subject to the usual caveats of force and misrepresentation, has no place to play within the product liability system. That assumption makes good sense in the few cases in which defective products are responsible for injuries to bystanders. But it is far more dubious when suits are brought by injured product purchasers or users. To be sure, there is typically no direct contract link between the manufacturer and ultimate purchaser. The absence of explicit contracts, however, is itself a reflection of the present body of legal rules that regulate product use. These rules refuse to enforce a limitation on liability or damages created by contract, and occasionally impose punitive damages on firms bold enough to seek contractual protection. If the law were otherwise, then a manufacturer could-and would-designate a retailer as his agent so as to secure a direct contract with a purchaser and, where possible, a product user. Contractual quiescence today is not a sign of satisfaction with the legal rules as ideal default provisions. Nor is it evidence that transactions costs are so high that voluntary agreements cannot be formed. It is only proof that any effort to contract out of the present tort system has been effectively blocked by the judges and legislatures who have created the modern law. The present regime of legal rules has powerful social consequences. The conventional economic assumption is that rational, self-interested parties only enter into contracts that ex ante assure them of some joint gain. By that standard, the present system of public regulation of contract terms, whether by common law decisions or statute, imposes significant losses on both sides. Legislation to remore these barriers to private contract could generate some substantial overall gains. Whenever legislation could generate some allocative improvement, it should be possible to divide the gains thereby generated to leave all interested parties better off than before. If the costs of passing legislation and dividing the gains were zero, then inefficient substantive rules would never remain on the public books. Today's product liability rules do not fade, but grow stronger with each passing year. The remainder of this paper helps to explain why this trend is likely to continue. The barriers to needed legislative reforms are simply too great.